Hurricane surge and inundation in the Bahamas, part 1: Storm surge model - Stephen Grey; Michael Turnbull; Jeffrey Simmons (Journal of Flood Risk Management)
Abstract A storm surge model has been developed as part of a pilot study for The Commonwealth of the Bahamas. The hydrodynamic model, TELEMAC‐2D, is used to simulate the response of water level to tide and the wind and atmospheric pressure fields of hurricanes and subsequent inundation over land. The model is used by The Bahamas Department of Meteorology to forecast storm surge and flooding over the islands of Grand Bahama and Eleuthera for incoming hurricanes to assist in preparation for and management of hurricane surge events and has been used in a flood risk assessment, reported in a companion paper. The model has been optimised to run quickly while also resolving the bathymetry and topography that affect the development and propagation of storm surge. Wind fields are generated within TELEMAC‐2D based on hurricane warning bulletins. The model has been validated for its representation of water level and against tide gauge measurements during four historical hurricanes: Irene, Sandy, Matthew and Dorian. Factors contributing to uncertainty in forecast predictions are discussed and recommendations are provided to improve the performance in future. The pilot study provides a template for future expansion to cover the other inhabited islands of The Bahamas.